Public Space Design in Museums - (:unkn) unknown (My University, 1982)
A manual which provides architects and museum professionals with information about visitor behavior, programming, and building design for art and natural history museums. Describes design principles that can improve the quality of the museum's public spaces. Supported in part by the American Institute of Architects Research Corporation. Highly illustrated.